2011
DOI: 10.1007/s10529-011-0747-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus limitation for the colony formation, growth and photosynthesis of an edible cyanobacterium, Nostoc sphaeroides

Abstract: The percentage of spherical colonies from the trichomes of Nostoc sphaeroides reached 62-73% after 16 days with 50 and 250 μM P, but only 10-15% at 0.5 and 5 μM P. During colony formation from microcolonies to macrocolonies, the growth rates were 95, 206 and 244% higher, respectively at 5, 50 and 250 μM P than that at 0.5 μM P. The light-saturated photosynthetic rate, maximum electron transport rate and light-limited photosynthetic efficiency at 0.5 μM P decreased, respectively, by 45, 51 and 32% than those at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Based on the studies described above, we selected N. sphaeroides colonies with diameters of 1–1.5 mm to construct the biohybrid system with InP nanomaterial (Figure 2a). Filaments of N. sphaeroides aggregate gradually into the microcolonies during the extended period of free settling, and this property had been utilized to construct the InP‐ N. sphaeroides biohybrid system [28b] . The InP nanomaterial was prepared (see the Experimental Section) and characterized for its morphology and photoelectrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the studies described above, we selected N. sphaeroides colonies with diameters of 1–1.5 mm to construct the biohybrid system with InP nanomaterial (Figure 2a). Filaments of N. sphaeroides aggregate gradually into the microcolonies during the extended period of free settling, and this property had been utilized to construct the InP‐ N. sphaeroides biohybrid system [28b] . The InP nanomaterial was prepared (see the Experimental Section) and characterized for its morphology and photoelectrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been suggested that P might play an important role in the growth and distribution of the N. sphaeroides in wild habitats (Mandal et al 1993;Qiu et al 2002;Chen et al 2012), and P availability is an important factor controlling phytoplankton productivity and species composition in lakes (Cotner and Wetzel 1992). Available phosphorus (AP) is the soluble PO 4 3− in soil absorbed by seasonal plants (Bao 2000).…”
Section: Discussionmentioning
confidence: 99%